Comparative Efficacy of Levetiracetam for Epilepsy in School-Aged Children with Intellectual Disability and Normal Intelligence - Ja Un Moon (MDPI AG, 2021)
Choosing optimal anti-seizure medication (ASM) is very important in pediatric patients with epilepsy who attend school, especially children with an intellectual disability (ID). Levetiracetam (LEV) has proven to be an effective, safe, generally well-tolerated, broad-spectrum ASM in children. In the context of increasing use of LEV in school-aged children with epilepsy and ID, we evaluate relevant clinical data, including efficacy, safety, and tolerability in children with epilepsy and an intellectual disability (ID) or normal intelligence (NI). We performed a retrospective chart review of children and included 298 pediatric patients with epilepsy who were treated with LEV with NI (147) and ID (151). After 6 months, 96% of NI and 83% of ID subjects had a seizure reduction rate greater than 50% (p = 0.031). The tolerability of LEV was generally good, with 75% retention rates at 2 years in both groups and only minor side effects (under 15%). The retention rates of patients with NI and ID were 76% and 74%, respectively (p = 0.597). Thus, LEV showed considerable efficacy with minimal side effects and high retention rates and is an easily maintained and safe treatment option for pediatric epilepsy with ID. However, better-designed research studies are needed to clearly elucidate the efficacy and safety of LEV in children with epilepsy and ID.